Subsequent meniscal tears following tibial tuberosity advancement and tibial plateau leveling osteotomy in dogs with cranial cruciate ligament deficiency: An in vivo experimental study. Issue 5 (29th April 2021) - Jeong, Jaemin; Jeong, Seong Mok; Kim, Stanley E.; Lewis, Daniel D.; Lee, Haebeom
Abstract: Objective: To evaluate the short‐ and mid‐term effects of tibial tuberosity advancement (TTA) and tibial plateau leveling osteotomy (TPLO) on subsequent meniscal tears. Study Design: Experimental in vivo study. Animals: Purpose‐bred beagle dogs ( n = 15). Methods: For each dog, the cranial cruciate ligaments were transected; one limb underwent TTA and the other limb underwent TPLO. Orthopedic and radiographic examinations were performed preoperatively and at 12 and 32 weeks postoperatively. Gross evaluation of the stifle joint was performed after euthanasia at 12 ( n = 10) and 32 ( n = 5) weeks. Results: Lameness scores were not different between TTA and TPLO limbs at any time point. Radiographic osteoarthritis scores of TTA stifles (1.33 ± 0.49) were higher than TPLO stifles (0.67 ± 0.49) ( p = .002) at 12 weeks postoperatively, but there was no difference between groups at 32 weeks postoperatively. Subsequent medial meniscal tears occurred in 6/10 TTA stifles, and 0/10 TPLO stifles at 12 weeks postoperatively and in 5/5 TTA stifles, and 1/5 TPLO stifles at 32 weeks postoperatively. Subsequent lateral meniscal tears occurred in 4/5 TTA stifles at 32 weeks postoperatively. Medial meniscal total gross pathology score was higher in TTA than TPLO stifles. TTA stifles had more articular cartilage damage when compared with TPLO stifles at 32 weeks postoperatively. Conclusion: In this within‐dog experimental comparison, subsequent medial meniscal tears and cartilage injury was more prevalent following TTA when compared to TPLO. Clinical significance: In an experimental model, TPLO protects the medial meniscus and articular cartilage better than TTA in stifles with complete cranial cruciate ligament deficiency.